Building on a human-centred, iterative, and agile co-design strategy to facilitate the availability of deep ocean data. (8th September 2022) - LaScala-Gruenewald, Diana E; Low, Natalie H N; Barry, James P; Brown, Jennifer A; King, Chad; Chavez, Francisco P; Ruhl, Henry A
Abstract: Current information on the status and trends of ocean change is needed to support effective and responsive management, particularly for the deep ocean. Creating consistent, collaborative and actionable mechanisms is a key component of the Deep Ocean Observing Strategy, a program of the United Nations Decade of Ocean Science for Sustainable Development. Here, we share an iterative, agile, and human-centred approach to co-designing datastreams for deep-sea indicators that serves stakeholders, including US National Marine Sanctuaries, presented as a four-phase project roadmap initially focused on the Monterey Bay National Marine Sanctuary, and then generalized to other areas such as the US West Coast, offshore wind development areas, and managed marine spaces globally. Ongoing efforts to provide key physical, biogeochemical, biological, and ecosystem variables for California's Marine Protected Areas are informing this co-design process. We share lessons learned so far and present co-design as a useful tool for (1) assessing the availability of information from deep ecosystems, (2) ensuring interoperability, and (3) providing essential information on the status and trends of indicators. Documenting and sharing this co-design strategy and scalable four-phase roadmap will further the aims of DOOS and other initiatives, including the Deep Ocean Stewardship Initiative and Challenger 150.